Caracterización de los pacientes menores de 15 años con tuberculosis en el Hospital Universitario San Vicente Fundación, 2011-2018 - Johanna Andrea Jaramillo-Zapata (Asociación Colombiana de Infectología, 2020)
Tuberculosis (TB) is the infectious disease that has caused the worst damage to the human species throughout history, both in terms of number of patients as well as deaths. It has been estimated that in the last 200 years, it has been responsible for the death of over 1 billion people (1). TB is currently one of the most important infectious diseases and it serves as a reflection of the huge economic and social differences that prevail in human population. Objective: To describe the demographic and clinical characteristics of patients younger than 15 years of age with TB from 2011 to 2018 in a fourth level hospital in Medellin - Colombia. Methodology: cross-sectional study of patients younger than 15 years of age who were evaluated and diagnosed with pulmonary and/or extra pulmonary TB at San Vicente de Paul University Hospital Foundation from January 2011 to December 2018. Results: A hundred-eighty patients with TB were included in the study, 71 (38,6 %) with pulmonary TB and 54 (29.3 %) with extra pulmonary TB. The most frequent clinical forms were lymph node compromise, central nervous system (CNS) infection and disseminated form. Thirty children (50 %) younger than 5 years of age had some degree of malnutrition. Microbiological confirmation by smear microscopy or culture was confirmed in 91 cases (49.4 %) and by Polymerase Chain Reaction (PCR) in 72 cases (39.1 %). Conclusions: Childhood TB requires a high index of suspicion; the sum of different criteria is essential for its diagnosis. However, an exhaustive search for the mycobacteria is a useful strategy to get an effective treatment.